Consistency of thromboelastometry analysis under scrutiny: Results of a systematic evaluation within and between analysers - Nagler, Michael; ten Cate, Hugo; Kathriner, Silvio; Casutt, Mattias; Bachmann, Lucas M.; Wuillemin, Walter A. (Thrombosis and Haemostasis, 2014)
While the use of thromboelastometry analysis (ROTEM®) in evaluation of haemostasis is rapidly increasing, important validity parameters of testing remain inadequately examined. We aimed to study systematically the consistency of thromboelastometry parameters within individual tests regarding measurements between different analysers, between different channels of the same analyser, between morning and afternoon measurements (circadian variation), and if measured four weeks apart. Citrated whole blood samples from 40 healthy volunteers were analysed with two analysers in parallel. EXTEM, INTEM, FIBTEM, HEPTEM and APTEM tests were conducted. A Bland-Altman comparison was performed and homogeneity of variances was tested using the pitman test. P-value ranges were used to classify the level of homogeneity (p<0.15 – low homogeneity, p = 0.15 to 0.5 – intermediate homogeneity, p>0.5 high homogeneity). Less than half of all comparisons made showed high homogeneity of variances (p>0.5) and in about a fifth of comparisons data distributions were heterogeneous (p<0.15). There was no clear pattern for homogeneity. On average, comparisons of MCF, ML and LI30 measurements tended to be better, but none of the tests assessed outperformed another. In conclusion, systematic investigation reveals large differences in the results of some thromboelastometry parameters and lack of consistency. Clinicians and scientists should take these inconsistencies into account and focus on parameters with a higher homogeneity such as MCF.Note: Part of the investigation was presented at the 56th meeting of the “Gesellschaft für Thrombose- und Hämostaseforschung (GTH)” in St. Gallen, Switzerland, February 1–4, 2012.
Keywords: Thromboelastometry; reliability; reproducibility